Urinary cystatin C levels as a diagnostic and prognostic biomarker in patients with acute kidney injury. Issue 4 (27th March 2013) - Park, Moo Yong; Choi, Soo Jeong; Kim, Jin Kuk; Hwang, Seung Duk; Lee, Yong Wha
Abstract Aim Acute kidney injury (AKI) is a frequent complication in critically ill patients and is associated with a high mortality. Clinicians have limited tools to predict the course of AKI at the time of serum creatinine increase. We evaluated the diagnostic and prognostic utility of urinary cystatin C (uCysC) in patients with AKI. Methods In this study, serum and uCysC and urinary creatinine (uCr) were measured in patients presenting with acute kidney injury. The patients were divided into two groups: those with prerenal AKI and those with an intrinsic AKI. Prerenal AKI was defined as a new‐onset increase in serum creatinine (sCr) that resolved within 72 h and returned to the baseline kidney function level. Patients with intrinsic AKI were defined and classified according to the Acute Kidney Injury Network (AKIN) criteria. Results Of the total number of patients (n = 213), 40.4% (n = 86) were judged to have prerenal AKI and 59.6% (n = 127) intrinsic AKI. uCysC values and the uCysC/uCr ratio were significantly higher in intrinsic AKI versus prerenal AKI. In intrinsic AKI, the uCysC concentration increased with AKI severity. The uCysC/uCr ratio was significantly higher in the RRT group versus the non‐RRT group (0.15 vs. 0.08, respectively; P = 0.037). In a multivariate analysis, the uCysC/uCr ratio was associated with in‐hospital mortality (P = 0.019). Conclusions uCysC level and the uCysC/uCr ratio were useful biomarkers of intrinsic AKI, and the uCysC/uCr ratio was predictive of in‐hospital death in AKI patients.